Advanced Google AdWords - Geddes, Brad (Serious skills., 2010)
Master Google AdWords and get more out of your campaigns. What's the secret to making every pay-per-click of your Google AdWords really pay? This must-have guide-written by a Google Advanced AdWords seminar instructor-shows you exactly how to apply advanced techniques and tactics for better results. Discover the best tools for keyword research, tips on crafting winning ad copy, advanced PPC optimization tricks, winning bidding strategies, and much more. If you manage AdWords PPC accounts, you won't want to miss this expert, detailed instruction.: Covers the essential and advanced capabilities.